Feminism in “Hustlers” Movie By Lorene Scafaria - Zazkia, Aulia Dela; Abdullah, Abdullah; Fitriyani, Fitriyani (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2024)
This study investigates the issues of feminism in Lorene Scafaria's "Hustlers" movie and explores the concept of women empowerment in the same context.Feminism is often interested in the way women are represented in the media. In "Hustlers", researchers might explore how female characters are portrayed, whether they are empowered or enslaved, whether they break traditional gender stereotypes, or whether they remain within stereotypical boundaries. Using Beauvoir's (2016) theory to analyze issues of feminism and Sushama Sahay's (1998) theory to analyze women's empowerment in film, this study adopts a qualitative descriptive approach. Through in-depth analysis, this study identified five liberal feminisms, three Marxist and socialist feminisms, three radical feminisms, five cultural feminisms, two economic feminisms, and five women's empowerments that appear in the context of "Hustlers". The findings provide rich insights into the representation of feminism in popular media and its contribution to the understanding of women in contemporary society.Keywords: Feminism, Women Empowerment, Hustlers.